2018
DOI: 10.1097/sap.0000000000001210
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lymphatic Drainage With a Self-Designed Surgical Approach Prolongs the Vascularized Skin Allograft Survival in Rats

Abstract: Vascularized composite allotransplantation (VCA) is an emerging treatment for significant tissue defects. However, VCAs usually consist of multiple highly antigenic skin tissues. Previous studies have shown that the lymphatic system in skin plays important roles in the initiation of immune responses during acute rejection, by transporting T cells and antigen-presenting dendritic cells to regional lymph nodes. Therefore, we designed a new surgical treatment to inhibit lymphatic drainage of skin allografts and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The capacity to isolate these peripheral and central modes of allosensitization can facilitate and trigger further experiments in VCA focusing on the manipulation of regional lymphatics and its effect on allograft outcomes. The latter is a subject of ongoing research in the field [16,17]. Several studies have demonstrated the critical nature of secondary lymphoid organs in organ allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to isolate these peripheral and central modes of allosensitization can facilitate and trigger further experiments in VCA focusing on the manipulation of regional lymphatics and its effect on allograft outcomes. The latter is a subject of ongoing research in the field [16,17]. Several studies have demonstrated the critical nature of secondary lymphoid organs in organ allograft rejection.…”
Section: Discussionmentioning
confidence: 99%